Conservation of biodiversity and poverty in Costa Rica: analysis by planning regions - Arroyo Zeledón, Michael Steven (2018)
One of the main strategies to preserve biodiversity has been the creation of protected areas, and some authors argue that such action will also have economic benefits for the human communities involved. Nevertheless, in several countries a spatial coincidence between these areas and poverty has been registered. This work evaluated whether there was more poverty in Costa Rican districts that have larger areas in inland national park or biological reserves. As an estimator of poverty in the districts, the Costa Rican index of social development (ISD) was used. For the whole country, districts with protected (DPA) areas had a lower ISD than those without them (DNPA). This result was also observed in the Central and Huetar Caribe planning regions; the opposite happened in the Huetar Norte region. The differences between planning regions offer opportunities for further research.